Morning Session Wednesday, June 28, 1978 (Rocky Mountain Coal Mining Institute, 1978)
Past President Shirl McArthur opened the meeting at 9:30 a.m. He called on the Auditing Committee to give its report. Stan Shubart, who checked the financia1 report of the treasurer, read the report. He asked that it be approved. A motion was made, seconded and carried. Shirl thanked all the committees for an excellent job in making this meeting a most successful one. Special thanks to Park Lamborn for a fine program and to Gussie Whiteside for all her efforts in behalf of the Institute. An increase in salary was voted for the secretary-treasurer. It was decided to return to Vail for the 1979 convention. The Resolutions Committee was called upon to give its report. Roy Coulson, Chairman, submitted the following: (I) RESOLVED, Whereas, in the year since the last convention of The Rocky Mountain Coal Mining Institute, the Institute and the coal mining industry have suffered the loss through death of the services of: O. F. Bridwell C. L. Book O. F. Lewis Frank Kolar O. H. Littrell L. B. Phillippi Weston L. Potter George C. Trevorrow